Demography, baseline disease characteristics and treatment history of patients with psoriasis enrolled in a multicentre, prospective, disease‐based registry (PSOLAR). (1st July 2014) - Kimball, A.B.; Leonardi, C.; Stahle, M.; Gulliver, W.; Chevrier, M.; Fakharzadeh, S.; Goyal, K.; Calabro, S.; Langholff, W.; Menter, A.
Summary: Background: Psoriasis is associated with several comorbidities and behavioural risk factors. Objectives: To evaluate demographic and disease characteristics in patients enrolled in the Psoriasis Longitudinal Assessment and Registry (PSOLAR). Methods: PSOLAR is a global, prospective, longitudinal, disease‐based registry that includes a postmarketing commitment to evaluate safety in patients with psoriasis. Enrolled patients had to be receiving, or be eligible to receive, conventional systemic or biological agents. Demographic/disease characteristics, medical histories, lifestyle risk factors and previous treatments are collected at enrolment. Efficacy and safety data are collected every 6 months for 8 years, and data are extracted annually. Selected parameters are evaluated by age quartile using post hoc analyses. Results: As of 23 August 2012, 11 900 patients were enrolled at 301 sites in North America, Europe and Latin America. Over half of the PSOLAR population (54·7%) is male, with a mean age of 48·6 years and mean body mass index of 30·9 kg m −2 at enrolment. Mean duration of disease at enrolment was 17·5 years, and mean Physician's Global Assessment score was 2·0. Psoriatic arthritis (35·5%) and cardiovascular diseases (38·2%) were highly prevalent. Diabetes mellitus type II was reported in 11·4% of patients. Depression and anxiety were noted in 14·7% and 11·1% of patients, respectively; 79·0% reported any alcohol use and 56·7% reported smoking or a history of smoking. The occurrence of most comorbidities, including cardiovascular disease and risk factors, increased with age. Conclusions: In the PSOLAR population, multiple and age‐appropriate comorbidities are associated with psoriasis and may affect the selection of psoriasis treatments.